The persistance of the effects of certain aspects of infantile experience on the behaviour of adult rats - Du Preez, Peter Derek (Department of Psychology, 2024)
Since Hunt's (1941) claim that he had introduced · a new field into the laboratory study of the animal - its 1• life history - there has been a spate of work in which the effects of many different kinds of variation have been studied. Though one may question the validity of Hunt's claim (see, for example, the early work of Conradi on singing birds, 1909) there is no doubt that this study of the effects of early food deprivation on subsequent hoarding has encouraged and perhaps given rise to a great number of other studies in this field. The importance of influences in childhood has long been acknowledged by authorities as diverse as Rousseau and Freud. The authority of embryological studies also lent weight to the opinion that early influence, by affecting development at its most formative and plastic period, might have more widespread and radical effects than equivalent influences later in life. In particular, it was supposed that traumatic experiences at an early stage of life might have results which were both more persistent and more extensive than t~aumatic experiences at a later stage. Again, the embryological analogy with its critical periods before structures became determined seemed to support this view. It is quite possible that all this is true, though it has been very imperfectly demonstrated. It is quite possible that there are psychological organisers which must act at certain critical periods of development; and it is quite possible that lack of these organisers will cause grave disorders in development. It is also possible that psychological lesions incurred early in life, by striking at the corner atones of psychological development, can cause very widespread effects.